Do Ethnic Dominoes Fall? Evaluating Domino Effects of Granting Territorial Concessions to Separatist Groups1. Issue 2 (29th January 2013) - Forsberg, Erika
Abstract : Forsberg, Erika. (2013) Evaluating Domino Effects of Granting Territorial Concessions to Separatist Groups. International Studies Quarterly, doi: 10.1111/isqu.12006 © 2013 International Studies Association There is a commonly expressed concern that granting territorial concessions to separatist groups may create "domino effects." However, although this statement is largely undisputed within political rhetoric, no firm conclusions have been provided in previous research. The purpose of this study is to systematically examine whether the granting of territorial concessions to an ethnic group does indeed spur new separatist conflicts. I suggest that such domino effects may be generated by two processes. First, the accommodation of an ethnic group's separatist demands may trigger a general inspiration process among other groups within and across borders. Second, by acquiescing to separatist demands, a government signals that it may also yield to the demands of other groups it confronts, making it more likely that other groups choose to pursue secessionism. Statistical analysis of data on territorial concessions globally 1989–2004 provides no evidence of domino effects. This holds true both within and across borders.